Enhanced Antibacterial Activity of Acinetobacter baumannii Bacteriophage ØABP-01 Endolysin (LysABP-01) in Combination with Colistin - Thummeepak, Rapee; Kitti, Thawatchai; Kunthalert, Duangkamol; Sitthisak, Sutthirat (Frontiers in Microbiology, 2016)
Endolysins are lytic enzymes produced by bacteriophages with their ability to degrade the cell wall of bacterial hosts. Endolysin (LysABP-01) from A. baumannii bacteriophage ØABP-01 was cloned, overexpressed and characterized. Endolysin LysABP-01 has a modular structure consisting of lysozyme-like (N-acetyl-β-d-muramidase) catalytic domain. It contains 185 amino acids which correspond to a 21.1 kDa protein. The lytic activity of the recombinant endolysin protein was determined by a plate lysis assay for its ability to lyse the autoclaved cell (crude cell wall) of the different bacterial species. LysABP-01 can degrade the crude cell wall of A. baumannii strains, Escherichia coli and Pseudomonas aeruginosa but not of Staphylococcus aureus. The antibacterial activity of LysABP-01 and its synergism with various antibiotics were tested. The results exhibited elevated antibacterial activity in a combination of the sub-MIC LysABP-01 and colistin. The checkerboard assay for measuring antibiotic synergy of LysABP-01 and colistin was performed. This combination was synergistic against various drug-resistant strains of A. baumannii (FIC index < 0.5). In summary, our study highlights the ability of LysABP-01 endolysin to hydrolyze the A. baumannii cell wall and its synergistic interaction with colistin.